Directing young dropouts via SMS: Evidence from a field experiment - Jérémy Hervelin (IZA Journal of Labor Policy, 2022)
Although short message services (SMS) are constantly used to transmit information, little is known about the use of SMS by public institutions to direct people. This paper presents a field experiment in France about the effectiveness of SMS in directing disadvantaged people toward public services. Two types of treatment SMS were provided: one type had its content written in a formal style; the second type SMS style was much informal. All the SMS were individualized and included specific information about the agencies. Results indicate that the SMS had no significant effect on enrollment. There is also no apparent heterogeneous effect according to individual, agency, or location characteristics. In line with other academic evidence, these findings suggest that SMS have very limited effectiveness in directing this population toward public services.
Keywords: D04; D83; D64; J68; 330; youth unemployment; information provision; public policy; field experiment